The European Union Looking for the Future. New Forms of Accountability and Governance - Emiliana Oana Tatarcan (CES Working Papers, 2016)
The European Union is more capable than any of its Member Stats, individually to meet the major challenges of the XXI century. It is a political and economic partnership that represents a unique form of cooperation among sovereign countries. The challenges can only be properly understood or addressed in a regional and global context. EU decision-making processes and the role played by the EU institutions vary depending on the subject under consideration. EU interests and values common to all its Member States and their defense on the international scene can be more effective with a common, the European approach, rather than a single voice in each state.
Keywords: 330; government; system; accountability; development; aid